PENGARUH PENGGUNAAN MODEL PROBLEM BASED LEARNING (PBL) TERHADAP KETERAMPILAN MENULIS BERITA - Syafitri, Windy; Arief, Ermawati; Noveria, Ena (Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2016)
ABSTRACT This research aims to (1) describe grade ability in writing news text without using PBL model, (2) describe grade ability in writing news text with using PBL model, and (3) describe the effect of the use of PBL model, toward students’ ability in writing news text. The type of this research is quantitative research done using experimental design. There are three results of the research are (1) the students’ ability in writing news text without using PBL model is low and grades C with average 67,38, (2) the students’ ability in writing news text with using PBL model is high and grades B with average 82,26, and (3) based on t-test, alternative hypothesis (H1) is gained at the significant phase 95% and degrees of freedom (df) = (n1+n2)-2 because tcount> ttable (5,659>1,67). Kata Kunci: pengaruh, model problem based learning, menulis berita